Core political values and the long-term shaping of partisanship - Evans, Geoffrey; Neundorf, Anja (Cambridge University Press, 2018)
Party identification has been thought to provide the central organizing element for political belief systems. We argue in contrast that core values concerning equality and government intervention versus individualism and free enterprise are fundamental orientations that can themselves shape partisanship. We evaluate these arguments in the British case with a validated multiple-item measure of core values, using ordered latent class models to estimate reciprocal effects with partisanship on panel data from the British Household Panel Study, 1991-2007. We demonstrate that core values are more stable than partisanship and have far stronger cross-lagged effects on partisanship than vice versa in both polarized and depolarized political contexts, for younger and older respondents, and for those with differing levels of educational attainment and income, thus demonstrating their general utility as decision-making heuristics.